Increasing CO2 changes community composition of pico- and nano-sized protists and prokaryotes at a coastal Antarctic site - Thomson, PG; Davidson, A; Maher, L (2016)
Ocean acidification is a globally recognised phenomenon, but little is known of its impacts on Antarctic marine microbes. Here we report on the community response of pico- and nanophytoplankton, heterotrophic nanoflagellates (HNF) and prokaryotes ( Archaea and Bacteria ) to elevated CO 2 during 3 minicosm experiments over the 2008/2009 summer at Davis Station, Antarctica. Coastal seawater was incubated in 650 l minicosms ( n = 6) for ≤ 12 d at CO 2 concentrations ranging from preindustrial levels to those predicted for 2100 and beyond. The abundance of pico- and nano-sized protists and prokaryotes were determined by flow cytometry, using chlorophyll autofluorescence to discriminate the phytoplankton, SYBR-Green to stain the prokaryotes and LysoTracker Green stain to discriminate the HNF. While the effects on nanophytoplankton abundance were inconclusive, our results show that increasing CO 2 can alter the composition of the microbial community in Antarctic coastal waters. Our 3 experiments consistently showed lower concentrations of HNF and higher abundances of picophytoplankton and prokaryotes in treatments exposed to elevated CO 2 . While the mechanism remains to be confirmed, our study suggests that CO 2 may reduce the mortality of picoplankton by HNF grazing. Our results indicate that changes in the composition of Antarctic microbial communities may occur within the concentration range of 750 to 1118 ppm CO 2 , potentially impacting the Antarctic food web through reduced food availability.